(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
Modern challenges require businesses to implement comprehensive measures for protecting assets and rights amid regulatory, digital, and geopolitical risks. This study analyzes changes in tax regulation, digital threats, and the need for technological and legal protection.